"Flying on empty" – effects of sleep deprivation on pilot performance. Issue 7 (2nd October 2020) - O'Hagan, Anna Donnla; Issartel, Johann; Wall, Aidan; Dunne, Friedrich; Boylan, Patrick; Groeneweg, Jaap; Herring, Matthew; Campbell, Mark; Warrington, Giles
ABSTRACT: Today's flight operations work on pressurised 24/7 timetables. As a result, sleep loss and fatigue are becoming commonplace among pilots and pose a serious threat to flight safety. This study examined the effects of 24 h' sleep deprivation on a variety of psychological measures, cognitive performance tasks and simulated flight. Seven commercial airline pilots completed the Samn-Perelli Crew Status Check (SPC), Profile of Mood States (POMS), Psychomotor Vigilance Task (PVT), Dual-N-Back, Rapid Visual Information Processing Task (RVP), NASA Task Load Index (NASA-TLX) and aviation-specific mathematical calculations as well as a computerised flight simulator task, during which participants were required to answer mid-flight fuel calculations and situational awareness questions (SA). Testing occurred at 3 hour intervals during the final 12 hours of a 24 hour period of continuous wakefulness. Significant impairments in performance were observed on nearly all tests following 20 hours continuous wakefulness. Flying performance was not significantly impaired. Changes in flight performance were found to be consistent with changes in situational awareness. Overall findings showed impairments in mood, cognition and flying performance following 20 hours continuous wakefulness. SA indicates promise as a potential indicator of changes in flying performance as a result of sleep deprivation and fatigue.